Diversity in U.S. mass media - Luther, Catherine A., 1962-; Lepre, Carolyn Ringer; Clark, Naeemah (Chichester, West Sussex : Wiley-Blackwell, 2012)
'Diversity in U.S. Mass Media provides comprehensive coverage of the evolution and issues surrounding portrayals of social groups within the mass media of the United States.Focuses on past and current mass media representations of social groups; Provides an overview of key theories that have guided research in mass media representations and stereotyping; Discusses the impact new media has on representation and how technology is giving a new voice to various social groups; Includes a chapter on how mass media industries are addressing diversity, complete with specially-commissioned interviews with media professionals; Offers helpful supplementary features such as a glossary, questions for reflection, suggestions for projects related to diversity in mass media, and online resources for both instructors and students; Accompanying website provides a glossary, links to related sites, recommendations of films to watch in the classroom, ideas for research projects, and an instructor's manual with sample syllabi'--
'Have Native-Americans always been portrayed accurately in books and films? What about historical depictions of African-Americans -- or women? Do contemporary newspapers accurately reflect the needs of the poor? For better or worse -- and too often, it's for the worse -- mass media depictions play a crucial role in shaping our views about individuals and social groups. Diversity in U.S. Mass Media offers comprehensive coverage of the evolution and myriad issues surrounding portrayals of social groups within the mass media of the United States. Issues addressed include representations of race/ethnicity, gender, sexual orientation, disability, and class in films, television, and the press. Also shown are ways in which new media have impacted such representations, including some of the innovative new Internet resources that are giving a voice to various social groups. By providing illuminating insights into the ways social groups are represented through the mass media, Diversity in U.S. Mass Media can help us immeasurably in gaining a better understanding of groups and individuals different from ourselves'--
Includes bibliographical references (p. [342]-355) and index.
Keywords: Minorities in mass media -- United States; Cultural pluralism in mass media -- United States; Mass media and minorities -- United States